Fire and Plant Diversification in Mediterranean-Climate Regions - Rundel, Philip W.; Arroyo, Mary T. K.; Cowling, Richard M.; Keeley, Jon E.; Lamont, Byron B.; Pausas, Juli G.; Vargas, Pablo (Frontiers in Plant Science, 2018)
Despite decades of broad interest in global patterns of biodiversity, little attention has been given to understanding the remarkable levels of plant diversity present in the world’s five mediterranean-type climate (MTC) regions, all of which are considered to be biodiversity hotspots. Comprising the Mediterranean Basin, California, central Chile, the Cape Region of South Africa, and southwestern Australia, these regions share the unusual climatic regime of mild wet winters and warm dry summers. Despite their small extent, covering only about 2.2% of world land area, these regions are home to approximately one-sixth of the world vascular plant flora. The onset of MTCs in the middle Miocene brought summer drought, a novel climatic condition, but also a regime of recurrent fire. Fire has been a significant agent of selection in assembling the modern floras of four of the five MTC regions, with central Chile an exception following the uplift of the Andes in the middle Miocene. Selection for persistence in a fire-prone environment as a key causal factor for species diversification in MTC regions has been under-appreciated or ignored. Mechanisms for fire-driven speciation are diverse and may include both directional (novel traits) and stabilizing selection (retained traits) for appropriate morphological and life history traits. Both museum and nursery hypotheses have important relevance in explaining the extant species richness of the MTC floras, with fire as a strong stimulant for diversification in a manner distinct from other temperate floras. Spatial and temporal niche separation across topographic, climatic and edaphic gradients has occurred in all five regions. The Mediterranean Basin, California, and central Chile are seen as nurseries for strong but not spectacular rates of Neogene diversification, while the older landscapes of southwestern Australia and the Cape Region show significant components of both Paleogene and younger Neogene speciation in their diversity. Low rates of extinction suggesting a long association with fire more than high rates of speciation have been key to the extant levels of species richness.